Formação inicial do professor de matemática: a (in)visibilidade dos saberes docentes - Cavalcante, Nahum Isaque dos Santos (2011)
This research strives to elucidate how they come about, the mobilization of teachers' knowledge, necessary to the professional practice of mathematics teachers, in the process of initial formation of the subjects advocated as pedagogical in undergraduate courses in mathematics. For the development of the research, we used an approach of qualitative investigation of the case study variety, where observation, not a participant, was our tool for data collection, which occurred in 2010, during a school semester of a undergraduate course in mathematics for teachers at a public institution of higher education. In this investigation, we placed ourselves as observers of school subjects, entitled Pedagogical Practice for the Teaching of Mathematics I and Pedagogical Practice for the Teaching of Mathematics II, where the choice of observing such courses took place because of our understanding that they feature the concern for developing in future teachers, a reflective practice, according to current educational trends in Mathematics Education. For the descriptions and data analysis, we chose to present them in narrative form, and for the theoretical support of our paper we use, among other authors who study teachers' professional practice and their relationships with teacher knowledge, Tardif (2008) and ―Their elements of the epistemology of professional practice‖. From the work accomplished, we can observe that a process of formation, be it initial or continued, has a greater chance of success when it can mobilize different teachers knowledge in a perspective, where it is known, that no theory of teacher education can cope with the complexity of the classroom, however, it is in the very formation, that real life experiences are fostered, that will complement the theory.